Azulene-based polybenzimidazole anion exchange membrane as well as preparation method and application thereof

By introducing aza-based structure into the polybenzimidazole material, the stability problem of the material in an alkaline environment and the ‘trade-off’ effect between anionic conductivity and dimensional stability are solved, and aza-based polybenzimidazole anion exchange membrane with high mechanical strength, alkaline stability and high conductivity is achieved.

CN119638996AActive Publication Date: 2025-03-18SHANGHAI JIAOTONG UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411902025.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-03-18
Estimated Expiration
2044-12-23

AI Technical Summary

Technical Problem

The polybenzimidazole materials in existing anion exchange membrane fuel cells are susceptible to anion attack in an alkaline environment, resulting in a short life and a ‘trade-off’ effect between anion conductivity and dimensional stability, affecting the mechanical and dimensional stability of the material.

Method used

By introducing aza-based structure, aza-based polybenzimidazole anion exchange membrane was designed, and the strong nucleophilicity of the aza-based group was used to improve the basic stability of the material, and polymers with high mechanical strength and thermal stability were prepared through polymerization and quaternization reactions.

Benefits of technology

Axyl polybenzimidazole anion exchange membrane with high OH-conductivity, alkaline stability and high mechanical strength has been achieved, which improves the dimensional stability and service life of the material, and is suitable for alkaline fuel cells and alkaline electrolytic cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119638996A_ABST
    Figure CN119638996A_ABST
Patent Text Reader

Abstract

The invention discloses an azulene-based polybenzimidazole anion exchange membrane as well as a preparation method and application thereof, and belongs to the technical field of membranes. According to the invention, through polymerization and quaternization reaction, a design thought of a novel polybenzimidazole polymer is provided, and a series of azulene-based polybenzimidazole alkaline anion exchange membranes, including linear and branched anion exchange membranes, are prepared. The introduction of the azulene group enriches the structure of the polybenzimidazole polymer, and the strong nucleophilicity of the polybenzimidazole polymer improves the alkaline stability of the membrane. In addition, polybenzimidazole containing an azulene group structure has relatively high mechanical strength and thermal stability, the water absorption rate and the expansion ratio are reduced, and the dimensional stability is improved. The azulene-based polybenzimidazole anion exchange membrane provided by the invention shows high OH <-> conductivity, alkaline stability and high mechanical strength, and can be used as an anion exchange membrane material for an alkaline fuel cell and an alkaline electrolytic tank.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of membrane technology, and specifically relates to an azulene-based polybenzimidazole anion exchange membrane and a preparation method and application thereof. Background Art

[0002] Hydrogen is essential for decarbonization and sustainable development. Anion exchange membrane fuel cells have received widespread attention in the industry because they do not rely on expensive precious metal (such as palladium) catalysts and can use low-alkaline electrolytes. Anion exchange membranes (AEMs) are key components of anion exchange membrane fuel cells and alkaline electrolyzers. Currently, the lack of AEMs with excellent comprehensive performance (alkaline stability, dimensional stability and conductivity) has hindered their commercial application. The main reason is that the increase in ion exchange capacity (IEC) and conductivity is often accompanied by higher water absorption (WU) and swelling rate (SR), which directly affects the dimensional stability and mechanical stability of the material, and thus affects the service life. Solving this "trade-off" effect is crucial to the development of AEMs.

[0003] Polybenzimidazole (PBI) is a class of heterocyclic glassy polymers containing benzimidazole as a repeating unit. They generally exhibit excellent chemical stability, ultra-high thermal stability (up to 400°C), inherent flame retardancy and excellent mechanical properties. In addition, the excellent electrical conductivity of PBIs makes it have great application potential in the direction of proton exchange membranes, which has become a prominent research field. However, PBIs-type materials are not yet mature in anion exchange membranes. The main problems faced by PBIs-type materials in this field are: (1) the "trade-off" effect between anion conductivity and dimensional stability; (2) susceptibility to anion attack in alkaline environments, resulting in a short lifespan; (3) limited structural selection makes it more difficult to change the above two properties.

[0004] Azulene, as an isomer of naphthalene, is composed of a fused electron-rich five-membered ring and an electron-deficient seven-membered ring, and has a very large dipole moment (1.08D). This special structure determines the physical and chemical properties of azulene, such as the narrow HOMO-LUMO energy gap and the anti-kasha fluorescence emission generated by the transition from S2 to S0. The strong nucleophilicity of the azulene group helps to improve the alkali resistance of polybenzimidazole polymers, and the rich azulene structure and substitution sites can greatly enhance the designability of the material structure, which is more conducive to the preparation of target polymers that match the application performance. Summary of the invention

[0005] The present invention provides an azulenyl polybenzimidazole anion exchange membrane, characterized in that the azulenyl polybenzimidazole anion exchange membrane contains an azulenyl polybenzimidazole polymer, and its structure is shown in Formula I:

[0006]

[0007] Among them, different A represents different types of PBI, B is an aromatic group, C is an azulene group, R is a different cationic group, and the value of n is between 0.01-1.

[0008] The present invention also provides a method for preparing the azulenyl polybenzimidazole anion exchange membrane, the method comprising the following steps:

[0009] (1) Synthesis of azulenyl polybenzimidazole precursor polymer: Dicarboxyl aromatic monomer R, dicarboxyl azulenyl monomer B, 3,3′-diaminobenzidine (DAP) or its derivatives are placed in a round-bottomed flask equipped with a stirrer, an inert gas inlet and a calcium chloride drying tube in a certain proportion. Add organic solvent α, purge with nitrogen, and then optionally add a small amount of catalyst β. The obtained mixed solution is stirred and reacted at 140-200°C. After a certain reaction time, the obtained viscous solution is poured into excess water for precipitation, and the obtained polymer solid is collected. The solid is neutralized with potassium carbonate solution (pH>7, preferably pH=7-9), then thoroughly washed with deionized water, and vacuum dried at 80°C for 24 hours to obtain azulenyl polybenzimidazole.

[0010] The structure is shown in Formula II:

[0011]

[0012] Among them, different A represents different types of PBI, B is an aromatic group, C is an azulenyl group, and the value of n is between 0.01-1.

[0013] (2) Synthesis of cationized azulenyl polybenzimidazole: Dissolve the azulenyl polybenzimidazole obtained in step 1 in organic solvent β, heat to dissolve it, add γ, and stir to react at 80°C for a period of time. Pour the solution after the reaction into water for precipitation, and finally wash with water, filter, collect and vacuum dry at 80°C for 24 hours.

[0014] (3) Preparation of azulenyl polybenzimidazole anion exchange membrane: The cationized azulenyl polybenzimidazole obtained in step 2 was dissolved in an organic solvent, stirred at room temperature and filtered, the filtrate was cast on a clean glass plate, the residual solvent was removed, and the film was carefully peeled off from the glass plate to obtain Cl - type membrane, and then Cl - The membrane was placed in KOH solution for ion exchange to obtain OH - The membrane was then washed with degassed deionized water under inert atmosphere to obtain an azulenyl polybenzimidazole anion exchange membrane.

[0015] In a preferred embodiment of the present invention, in step (1), the molar ratio of C to B is 1:1-99, and the molar ratio of B+C to DAP (or its derivative) is 1:0.9-1.2.

[0016] In another preferred embodiment of the present invention, in step (1), the organic solvent α is selected from at least one of N,N-dimethylformamide, dimethyl sulfoxide and polyphosphoric acid.

[0017] In another preferred embodiment of the present invention, in step (1), the catalyst is selected from at least one of phosphorus pentoxide, polyphosphoric acid, and methanesulfonic acid.

[0018] In another preferred embodiment of the present invention, in step (2), the organic solvent is selected from at least one of acetonitrile, tetrahydrofuran, N-methylpyrrolidone, dimethyl sulfoxide, N,N-dimethylacetamide, N,N-dimethylformamide or sulfolane.

[0019] The present invention also provides an azulenyl polybenzimidazole anion exchange membrane prepared by the above-mentioned preparation method.

[0020] The present invention also provides a use of the azulenyl polybenzimidazole anion exchange membrane in the preparation of a fuel cell or an alkaline electrolytic cell.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] The present invention provides a novel design concept of polybenzimidazole polymer through polymerization and quaternization reaction, and prepares a series of azulene-based polybenzimidazole alkaline anion exchange membranes, including linear and branched types. The introduction of azulene groups enriches the structure of polybenzimidazole polymers, and its strong nucleophilicity improves the alkaline stability of the membrane. In addition, the polybenzimidazole containing azulene structure has high mechanical strength and thermal stability, reduced water absorption and expansion ratio, and improved dimensional stability.

[0023] The azulene-based polybenzimidazole anion exchange membrane provided by the present invention exhibits high OH - Due to its high conductivity, alkaline stability and high mechanical strength, it can be used as anion exchange membrane material for alkaline fuel cells and alkaline electrolytic cells.

[0024] After optimization, the azulene-based polybenzimidazole anion exchange membrane of the present invention has high OH - Electrical conductivity (80℃, OH - Conductivity>100mS cm -1 ), high mechanical strength (tensile strength>35MPa, elongation at break>10%), high dimensional stability, good processability, and excellent alkaline stability in 1M KOH at 80°C (>500h). BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 The figure is a test result diagram of water absorption of each embodiment and comparative example;

[0026] Figure 2 The figure is a test result diagram of the swelling ratio of each embodiment and comparative example;

[0027] Figure 3 The test results of the conductivity of each embodiment and comparative example are shown in FIG.

[0028] Figure 4 The following are the alkaline electrolyzed water MEA test results of various embodiments and comparative examples. DETAILED DESCRIPTION

[0029] The specific implementation of the present invention is further described below in conjunction with the technical solution.

[0030] The following are various exemplary embodiments of the present invention, which should not be considered as limitations of the present invention, but should be understood as more detailed descriptions of certain aspects, characteristics and embodiments of the present invention. It should be understood that the terms described in the present invention are only for describing specific embodiments and are not intended to limit the present invention.

[0031] In addition, for the numerical range in the present invention, it is understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0032] Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which the invention pertains. Although only preferred methods and materials are described herein, any methods and materials similar or equivalent to those described herein may also be used in the practice or testing of the present invention.

[0033] The terms "include", "comprising", "having", "containing", etc. used herein are all open-ended terms, which mean including but not limited to. The synthesis method used in the present invention is a conventional synthesis method in the art, and the composition structure of the product can be inferred from the raw materials used.

[0034] The test methods used in the following examples are:

[0035] Performance Testing:

[0036] The equipment and testing methods involved in the embodiment are as follows:

[0037] Polymer structure characterization: AVANCE III HD 400 (400M) liquid nuclear magnetic resonance was used to test the hydrogen spectrum of the polymer ( 1 H NMR) and carbon spectroscopy ( 13 C NMR). The infrared spectrum of the polymer was measured using a PerkinElmer Spectrum 100 Fourier transform infrared spectrometer. The molecular weight of the polymer was characterized using a normal temperature gel permeation chromatograph model Z-1601 produced by Tosoh Corporation of Japan.

[0038] Ion Exchange Capacity (IEC) Test Method: Br of Azulenyl Polybenzimidazole Polymers - or I - The membrane was dried in a vacuum oven at 75°C and the mass was weighed to record the weight of the dry film. The membrane was soaked in 25 mL of 0.2 M NaNO3 solution for 6 hours, repeated three times, and the NaNO3 solution after ion exchange was collected. The indicator potassium chromate solution (20 mL, 0.01 M) was added to the solution, and titrated with 0.01 M AgNO3 standard solution. When a brick-red precipitate appears and does not disappear after shaking, the titration is complete. Record the volume of AgNO3 solution consumed. The product of the concentration and volume of the AgNO3 solution divided by the mass of the dry film is the IEC.

[0039] Conductivity test: The electrochemical workstation used was produced by Shanghai Chenhua Instrument Co., Ltd., model CHI660E. The conductivity of the branched membrane at different temperatures was tested by the alternating current impedance method (EIS). The measured potential amplitude was 10mV. In order to reduce the error caused by the contact resistance to the measurement results, the resistance tested was the in-plane resistance of the membrane sample. In the experiment, the membrane was cut into a size of 40mm×10mm, placed in a fixture, and the fixture was placed in pure water. The test temperature ranged from 30℃ to 80℃, and the membrane resistance was tested every 10℃. It was necessary to keep warm for 1h before the test. Finally, the ionic conductivity σ of the sample was calculated according to the formula: σ=l / (wdR) where l is the length of the membrane between the electrodes (cm), w is the width of the membrane (cm), d is the thickness of the membrane (μm), and R is the measured membrane resistance (mΩ).

[0040] Alkaline fuel cell performance test: The instrument used was produced by Scribner Associates Co., USA, and the instrument model was 850e multi-range fuel cell test system, and the test was conducted in current mode. The test conditions were H2 and O2 atmospheres, test temperatures of 60℃ and 80℃, and H2 and O2 flow rates were both 200mL / min.

[0041] Tensile strength test: Instron M3300 electronic universal testing machine was used to test the dry film sample 5×0.5 cm (length×width) at a tensile rate of 5 mm / min.

[0042] Alkaline stability test: The prepared anion membrane was immersed in NaOH solutions of different concentrations (1, 2, 5, 10 M) at different temperatures (20, 30, 40, 50, 60, 70, 80°C), and its conductivity was measured at the same time. The alkaline stability was analyzed by the change in the conductivity of the electrolyte membrane.

[0043] Anion exchange membrane water electrolysis performance test: anode is loaded with IrO2 (1mg / cm 2 ) titanium felt, the cathode is Pt / C (1 mg / cm 2 ) carbon paper, Nafion as a conductive agent and binder, with a content of 0.5wt%, and an electrode area of ​​4cm 2 The MEA electrolytic cell was assembled, the electrolyte was 1M KOH, the circulation rate was 20mL / min, and the test temperature was 60°C. The test instrument was CHI660e, and a 0-2V linear voltammetric sweep test was performed on the electrolytic cell.

[0044] Example 1

[0045] Preparation of 1,3-azulenyl polybenzimidazole (p-PBI-Az-n) anion exchange membrane:

[0046] (1) Synthesis of 1,3-azulenyl polybenzimidazole precursor polymer (p-PBI-Az-n): Taking the synthesis of p-PBI-Az-1 as an example, 3,3'-diaminobenzidine (2.15 g, 10.03 mmol), terephthalic acid (1.65 g, 9.93 mmol), and 1,3-azulenedicarboxylic acid (0.022 g, 0.10 mmol) were placed in a round-bottomed flask equipped with a stirrer, an inert gas inlet, and a calcium chloride drying tube. Polyphosphoric acid (83.50 g) was added and purged with nitrogen. The obtained mixed solution was stirred and reacted at 180°C for 48 h. The obtained viscous solution was poured into 300 mL of water for precipitation, and the obtained polymer solid was collected. The solid was neutralized with potassium carbonate solution (300 mL, 1.0 M) (pH = 7.4), then washed with deionized water, and dried under vacuum at 80° C. for 24 h to obtain black solid p-PBI-Az-1 (polymer structure confirmed by NMR and IR; polymer weight average molecular weight 24.5 kDa), y = 87% (Yield). Wherein, n = 1 means that the content of 1,3-azulenedicarboxylic acid accounts for 10% of the total dicarboxyl monomer content.

[0047]

[0048] (2) Synthesis of functionalized 1,3-azulenyl polybenzimidazole (p-PBI-Az-n-Br): p-PBI-Az-1-Br is also used as an example. 1.0 g of the prepared 1,3-azulenyl polybenzimidazole material (p-PBI-Az-1) was dissolved in 60 mL of dimethyl sulfoxide (DMSO), heated to 80°C to dissolve, and then 1.16 g of 1,3-dibromopropane was added. The mixture was reacted at 80°C for 4 h. After cooling to room temperature, 20 ml of 25 wt% trimethylamine solution was added and the mixture was reacted for 24 h. The solution after the reaction was poured into water for precipitation, and finally washed with water, filtered, and dried under vacuum at 80°C for 24 h to obtain the functionalized polymer p-PBI-Az-1-Br, y=89%.

[0049]

[0050] (3) Preparation and ion exchange of p-PBI-Az-n-OH anion exchange membrane: p-PBI-Az-1-Br (1 g) in step (2) was dissolved in 30 mL DMSO, the polymer solution was filtered through a 0.45 μm polytetrafluoroethylene filter membrane, and the filtrate was cast on a clean glass plate. Subsequently, the solution was evaporated at 80°C for 12 h, evaporated at 120°C for 12 h, and vacuum dried at 120°C for 24 h to completely remove the residual solvent. Br was peeled off from the glass plate. - The membrane was ion exchanged in 1M KCl solution at 80°C for 12 h, and then washed three times with deionized water to remove the residual salt and obtain Cl - The membrane was placed in 1M KOH solution at 80°C for 12 h for ion exchange, and then washed three times with deionized water under nitrogen atmosphere to obtain OH - Type film. Film thickness 50μm.

[0051] Example 2

[0052] Preparation of 3,3'-dicarboxy-1,1'-biazulyl polybenzimidazole (p-PBI-biAz-n) anion exchange membrane:

[0053] (1) Synthesis of 3,3'-dicarboxyl-1,1'-biazulyl polybenzimidazole precursor polymer (p-PBI-biAz-n): Taking the synthesis of p-PBI-biAz-1 as an example, 3,3'-diaminobenzidine (2.15 g, 10.03 mmol), terephthalic acid (1.5 g, 9.03 mmol), and 3,3'-dicarboxyl-1,1'-biazulyl (0.344 g, 0.10 mmol) were placed in a round-bottomed flask equipped with a stirrer, an inert gas inlet, and a calcium chloride drying tube. Polyphosphoric acid (83.50 g) was added and purged with nitrogen. The obtained mixed solution was stirred at 200°C for 48 h. After a certain reaction time, the obtained viscous solution was poured into 200 mL of water for precipitation, and the obtained polymer solid was collected. The solid was neutralized with potassium carbonate solution (300 mL, 1 M), then thoroughly washed with deionized water, and dried under vacuum at 80° C. for 24 h to obtain black solid p-PBI-biAz-1 (polymer structure confirmed by NMR and IR; polymer weight average molecular weight 25.5 kda), y=87%. Where n=1 means that the content of 3,3'-dicarboxylic acid-1,1'-biazulene accounts for 10% of the total dicarboxyl monomer content.

[0054]

[0055] (2) Synthesis of functionalized 3,3'-dicarboxyl-1,1'-biazulyl polybenzimidazole p-PBI-biAz-n-Br: p-PBI-biAz-1-Br is also used as an example. The same as step (2) of Example 1 (the process and conditions are the same as step (2) of Example 1) to obtain a functionalized polymer p-PBI-biAz-1-Br, y = 85%.

[0056]

[0057] (3) Preparation of p-PBI-biAz-n-OH anion exchange membrane and ion exchange: Taking p-PBI-biAz-1-OH as an example, the same as step (3) of Example 1 (the process and conditions are the same as step (3) of Example 1) to obtain OH - Type membrane.

[0058] Example 3

[0059] Preparation of 3,3"-dicarboxylic acid-1,1':3',1"-triazulyl polybenzimidazole (p-PBI-triAz-n-OH) anion exchange membrane:

[0060] (1) Synthesis of 3,3"-dicarboxylic acid-1,1':3',1"-triazulyl polybenzimidazole precursor polymer (p-PBI-triAz-n): Taking the synthesis of p-PBI-triAz-1 as an example, 3,3'-diaminobenzidine (2.15 g, 10.03 mmol), terephthalic acid (1.33 g, 8.03 mmol), and [1,1':3',1"-triazulyl]-3,3"-dicarboxylic acid (0.47 g, 1.00 mmol) were placed in a round-bottom flask equipped with a stirrer, an inert gas inlet, and a calcium chloride drying tube. Polyphosphoric acid (83.50 g) was added and purged with nitrogen. The obtained mixed solution was stirred and reacted at 200°C for 48 h. After a certain reaction time, the obtained viscous solution was poured into 200 mL of water for precipitation, and the obtained polymer solid was collected. The solid was neutralized with potassium carbonate solution (300 mL, 1 M), then thoroughly washed with deionized water, and dried under vacuum at 80° C. for 24 h to obtain black solid p-PBI-triAz-1 (polymer structure confirmed by NMR and IR; polymer weight average molecular weight 30.1 kDa), y=81%. Wherein, n=1 means that the content of [1,1':3',1"-triazulyl]-3,3"-dicarboxylic acid accounts for 10% of the total dicarboxyl monomer content.

[0061]

[0062] (2) Synthesis of functionalized 1,1',3,3'-tetracarboxyl-6,6'-biazulyl polybenzimidazole (p-PBI-triAz-n-Br): p-PBI-triAz-1-Br is also used as an example. The same as step (2) of Example 1 (the process and conditions are the same as step (2) of Example 1) to obtain a functionalized polymer p-PBI-triAz-1-Br, y = 93%.

[0063]

[0064] (3) Preparation of p-PBI-triAz-n-OH anion exchange membrane and ion exchange: The same as step (3) in Example 1 (the process and conditions are the same as step (3) in Example 1) to obtain p-PBI-triAz-1-OH membrane.

[0065] Comparative Example 1

[0066] Preparation of polybenzimidazole anion exchange membrane (p-PBI), the preparation method (process and conditions) is the same as Example 1, except that no azulene carboxylic acid monomer (1,3-azulene dicarboxylic acid, 3,3'-dicarboxylic acid-1,1'-biazulene and 1,1',3,3'-tetracarboxylic acid-6,6'-biazulene, etc.) is added in the polymerization step.

[0067] The test results show that the p-PBI-Az-1 anion exchange membrane prepared in Example 1 has an OH - The conductivity is 121 mS / cm, the anion exchange capacity is 1.81 mmol / g, the swelling rate is 22%, and the alkaline stability is maintained for 500 h in 1 M KOH at 80°C. - The conductivity is 135 mS / cm, the anion exchange capacity is 2.01 mmol / g, the swelling rate is 23%, and the alkaline stability is maintained for 600 h in 1 M KOH at 80°C. - The conductivity is 156mS / cm, the anion exchange capacity is 2.22mmol / g, the swelling rate is 25%, and the alkaline stability is maintained for 1000h at 80℃ and 1MKOH. - The conductivity is only 103mS / cm, the anion exchange capacity is 1.61mmol / g, the swelling rate is 19%, and the alkaline stability is maintained for 300h in 80°C and 1M KOH. The results show that the performance of the anion exchange membrane prepared in the comparative example is significantly reduced compared with the anion exchange membrane prepared in the example. Figure 1-3 The test results of water absorption, swelling rate and conductivity of each embodiment and comparative example are shown in FIG. Figure 4 The following are the alkaline electrolyzed water MEA test results of various embodiments and comparative examples.

[0068] The preferred specific embodiments of the present invention are described in detail above. It should be understood that ordinary technicians in the field can make many modifications and changes based on the concept of the present invention without creative work. Therefore, all technical solutions that can be obtained by technicians in the technical field based on the concept of the present invention through logical analysis, reasoning or limited experiments on the basis of the prior art should be within the scope of protection determined by the claims.

Claims

1. An azulene-based polybenzimidazole anion exchange membrane, characterized in that: The raw material used is or contains azulenyl polybenzimidazole polymer, and its structure is shown in Formula I: Wherein, different A represents different types of PBI groups, B is an aromatic group, C is an azulene group, R is a different cationic group, and the value of n is between 0.01 and 1, representing the ratio of the molar number of n and the two corresponding groups in brackets (1-n) (the total molar number of the two groups in brackets in the polymer is 1); A is one or more of the following structures: No A group (adjacent benzene rings are directly connected), B is one or more of the following structures: C is one or more of the following structures: The four Rs are independently one or more of the following structures: In the group R, n is an integer greater than or equal to 0 (preferably 0-4, more preferably 5-8) The wavy lines in the above structure Represents a connection.

2. The azulene-based polybenzimidazole anion exchange membrane according to claim 1, characterized in that: The weight average molecular weight of the azulenyl-containing polybenzimidazole polymer of formula I is in the range of 1.0-10.0 kda; the film thickness is 10-200 μm, and the polymerization mode of the groups in brackets corresponding to n and (1-n) is random polymerization.

3. A method for preparing the azulenyl polybenzimidazole anion exchange membrane according to claim 1 or 2, the preparation method comprising the following steps: (1) Synthesis of azulenyl polybenzimidazole precursor polymer: A dicarboxylic aromatic monomer B-(COOH)2 (the specific structure of B is the same as the corresponding group B structure in claim 1, which is one or more of the corresponding group B structures in claim 1; preferably, it can be one or more of terephthalic acid, isophthalic acid, 5-methylisophthalic acid, 2,3,5,6-tetramethylterephthalic acid, 5-tert-butyl-1,3-benzenedicarboxylic acid, etc.), a dicarboxylic azulene monomer C-(COOH)2 (the specific structure of C is the same as the corresponding group C structure in claim 1, which is one or more of the corresponding group C structures in claim 1; preferably, it can be one or more of 1,3-azulenedicarboxylic acid, 6-methylazulene-1,3-dicarboxylic acid, 6-phenylazulene-1,3-dicarboxylic acid, [1,1'-biazulene]-3,3'-dicarboxylic acid, etc.), 3,3' -diaminobenzidine (DAP) or its derivatives (which may be one or more of 4,4'-oxybis(1,2-phenylenediamine), 4,4'-sulfonylbis(1,2-phenylenediamine), [1,1':3',1"-terphenyl]-3,3",4,4"-tetraamine, 4,4'-(4-phenylpyridine-2,6-diyl)bis(benzene-1,2-diamine), etc.) are placed in a container, an organic solvent α is added, an inert atmosphere gas (such as nitrogen and / or argon) is purged, and then a catalyst β is added; the obtained mixed solution is stirred and reacted at 140-220° C., the obtained solution is poured into water for precipitation, and the obtained polymer solid is collected; the solid is neutralized with potassium carbonate solution to be alkaline (pH>7, preferably pH=7-9), then washed with water, and dried to obtain azulenyl polybenzimidazole (the structure is shown in Formula I); (2) Synthesis of cationized azulenyl polybenzimidazole: dissolve the azulenyl polybenzimidazole obtained in step (1) in an organic solvent β, heat to dissolve it, add a γ reagent with a cationic group, heat in a dark place (room temperature - 120°C, preferably 50-80°C) and stir to react; put the obtained solution into water for precipitation, wash the obtained solid with water, and dry to obtain cationized azulenyl polybenzimidazole; (3) Preparation of azulenyl polybenzimidazole anion exchange membrane: dissolve the cationized azulenyl polybenzimidazole obtained in step (2) in an organic solvent, stir and filter at room temperature, cast the filtrate on a flat plate (such as a glass plate), remove the solvent, and then peel off the film from the plate to obtain Br - or I - Type membrane, then Br - or I - The membrane was placed in KOH solution for ion exchange to obtain OH - The membrane is then washed with water under an inert atmosphere (such as nitrogen and / or argon) to obtain an azulenyl polybenzimidazole anion exchange membrane.

4. The preparation method according to claim 3, characterized in that: In step (1), the molar ratio of C-(COOH)2 and B-(COOH)2 is 1:1-99, preferably 1:2; the molar ratio of B-(COOH)2+C-(COOH)2 and DAP (or its derivative) is 1:0.9-1.2, preferably 1:1.

05.

5. The preparation method according to claim 3, characterized in that: In step (1), the organic solvent α is selected from at least one or more of N,N-dimethylformamide, dimethyl sulfoxide, and polyphosphoric acid; The mass concentration of B-(COOH)2+C-(COOH)2 therein is 0.01-1 mg / ml, preferably 0.1-0.3 mg / ml.

6. The preparation method according to claim 3, characterized in that: In step (1), the catalyst β is selected from one or more of phosphorus pentoxide, polyphosphoric acid, and methanesulfonic acid; The usage ratio of the compound to B-(COOH)2+C-(COOH)2 is 1:0.01-100, preferably 1:30-50.

7. The preparation method according to claim 3, characterized in that: In step (2) or (3), the organic solvent β is selected from at least one or more of acetonitrile, tetrahydrofuran, N-methylpyrrolidone, dimethyl sulfoxide, N,N-dimethylacetamide, N,N-dimethylformamide or sulfolane; In step (2), the mass concentration of azulenyl polybenzimidazole dissolved in the organic solvent β is 0.01-100wt%, preferably 30-50wt%; The heating dissolution temperature is 20-120°C, preferably 60-80°C; the mass ratio of the γ reagent to the azulene polybenzimidazole is 0.1-100:1, preferably 20-50:1; the reaction is stirred at room temperature in the dark for 1-100h, preferably 12-48h; the γ reagent is one or more of the following structures: Wherein, X is at least one or two of Br or I, and n is an integer greater than or equal to 0 (preferably 0-4, more preferably 5-8).

8. The preparation method according to claim 3, characterized in that: In step (3), the concentration of the KOH solution is 0.1-5M / L, preferably 0.5-2M.

9. An azulene-based polybenzimidazole anion exchange membrane prepared by the preparation method according to any one of claims 3 to 8.

10. Use of the azulenyl polybenzimidazole anion exchange membrane according to claim 1 or claim 9 as a diaphragm in a fuel cell or an alkaline electrolytic cell.

Citation Information

Patent Citations

  • Polybenzoimidazole-poly (ionic liquid) cross-linked composite high temperature proton exchange membrane and preparation method thereof

    CN107248583A

  • Comb structure high-conductivity polybenzimidazole anion exchange membrane and preparation method thereof

    CN110112448A

  • Bicyclic ammonium ion polybenzimidazole, anion exchange membrane, and preparation methods and applications of discloses bicyclic ammonium ion polybenzimidazole and anion exchange membrane

    CN110527088A

  • Blend membranes based on polybenzimidazole (PBI) and polymeric ionic liquids (PILS) and a process for the preparation thereof

    US20160340484A1